Cittadinanza globale versus (dis)ordine mondiale. Un’analisi critica - Picchio, Marta (SocietàMutamentoPolitica, 2016)
For a long time, the reflection on the theme of global citizenship has interested institutions and intellectuals committed to give answers to humanitarian crises. The primary purpose of this essay is to give back a realistic image of rights’ denial. The second purpose of this essay is to inquiry about the dynamics which give rise to global inequalities. At last our aim is to show the first real occurring signs of change in the global geopolitical panorama. The most evident result of this change is the more and more important role of the continental and supranational unions which are helping us to build the global citizenship; the second element regards the activities concerning the Global Citizenship Education (gced); the third change has to do with the massive programs and donations from the nonprofit organization (npo); the fourth and last evidence is all what concerns the newborn Fourth Industrial Revolution and the potential of technological innovations.